Perceived benefits and health risks of cigarette smoking among young adults: insights from a cross-sectional study - Umesh Raj Aryal; Dharma Nand Bhatta (Tobacco Induced Diseases, 2015)
Background Perceptions of smoking-related health risks and benefits among young adults (18–24 years) and their smoking behaviour have not been adequately studied in low-income countries like Nepal. This study has examined the perceived risks and the benefits of smoking among young adults who smoke vs. don’t smoke.